2001
DOI: 10.1093/molehr/7.11.1085
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of cyclin D1 and oestrogen receptor (alpha and beta) levels in human leiomyoma and adjacent myometrium

Abstract: The aim of these experiments was to investigate the expression of cyclin D1 and of oestradiol receptors as well as the level of [(3)H]oestradiol binding in leiomyoma and adjacent myometrium from human uteri at different menstrual phases and at an early stage of menopause. [(3)H]oestradiol binding was determined by saturation analysis, while the oestradiol receptor (ER) alpha and beta and cyclin D1 levels were determined by Western blot analysis of 16 samples of human leiomyomas and corresponding myometria at d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
46
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 34 publications
7
46
0
1
Order By: Relevance
“…For example fibronectin 1, which in our study was significantly upregulated in fibroids with four independent probe sets, has been reported as downregulated in fibroids in a microarray study containing only six fibroid samples (Chegini et al, 2003). The changes in the expression profiles observed between normal myometrium and fibroid tissue also confirmed some previously reported results (Kovacs et al, 2001;Tsibris et al, 2002;Ahn et al, 2003;Chegini et al, 2003;Wang et al, 2003;Weston et al, 2003). For example, CCND1, endothelin receptor type A (EDNRA), collagen type III alpha 1 (COL3A1), and collagen type IV alpha 2 (COL4A2) were upregulated, and early growth response 1 (EGR1), complement component 1r (C1R), actin binding LIM protein 1 (ABLIM1), v-jun sarcoma virus 17 oncogene homolog (JUN), and B-cell CLL/lymphoma 6 (BCL6) were downregulated in fibroids.…”
Section: Discussionsupporting
confidence: 91%
“…For example fibronectin 1, which in our study was significantly upregulated in fibroids with four independent probe sets, has been reported as downregulated in fibroids in a microarray study containing only six fibroid samples (Chegini et al, 2003). The changes in the expression profiles observed between normal myometrium and fibroid tissue also confirmed some previously reported results (Kovacs et al, 2001;Tsibris et al, 2002;Ahn et al, 2003;Chegini et al, 2003;Wang et al, 2003;Weston et al, 2003). For example, CCND1, endothelin receptor type A (EDNRA), collagen type III alpha 1 (COL3A1), and collagen type IV alpha 2 (COL4A2) were upregulated, and early growth response 1 (EGR1), complement component 1r (C1R), actin binding LIM protein 1 (ABLIM1), v-jun sarcoma virus 17 oncogene homolog (JUN), and B-cell CLL/lymphoma 6 (BCL6) were downregulated in fibroids.…”
Section: Discussionsupporting
confidence: 91%
“…The opposing action and dominance of ERb over ERa in E 2 activation of both ERE-dependent and AP1-dependent gene expression supports a role for ERb as a dominant negative inhibitor of the proliferative and antiapoptotic effects of E 2 through ERa. In line with this notion, it has been proposed that the modulation of ERa-dependent cyclin D1 expression by ERb could be defective in leiomyomas (34). Our data provide a mechanistic basis as to how this might come about, because they show that in leiomyomas with a high ERa-to-ERb ratio, formation of ERa homodimers is increased substantially, and this may cause the opposing action of ERb on, for example, ERa-mediated activation of cyclin D1 gene expression to decrease accordingly, with potentially pronounced implications as regards tumor growth.…”
Section: Figurementioning
confidence: 93%
“…There is clear evidence that aberrant estrogen receptor signaling contributes to leiomyoma development and growth. For example, leiomyomas overexpress ERα and ERβ mRNA compared with surrounding myometrium (27,28). In addition, Maekawa and colleagues (29) demonstrated that epigenetic regulation of ERα through DNA methylation plays a role in leiomyoma.…”
Section: Steroid Signaling Estrogenmentioning
confidence: 99%